Analisis Hubungan Intensitas Menonton YouTube dengan Kesantunan Berbahasa: Studi Korelasi pada Anak Usia 4–6 Tahun - Siska Amaliyah; Taopik Rahman; Purwati Purwati (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The advancement of digital technology has made YouTube an integral part of early childhood routines, serving as both entertainment and a source of visual information. This study aims to analyze the relationship between the intensity of YouTube viewing and language politeness among children aged 4 to 6 years in Tawang District, Tasikmalaya City. A quantitative correlational approach was employed, involving 178 children selected through purposive sampling. Data were collected using a structured questionnaire based on indicators of viewing intensity (frequency, duration, type of content) and principles of politeness in language. Instrument validity and reliability tests confirmed that the questionnaire was appropriate for data collection. Results showed that most children had moderate to high viewing intensity, predominantly watching entertainment content. Pearson correlation analysis revealed a positive and statistically significant relationship between YouTube viewing intensity and children's language politeness (r = 0.313; p = 0.000), although the strength of the relationship was categorized as low. These findings support cultivation theory, which posits that prolonged exposure to media can shape social behaviors, including the use of polite language. Therefore, YouTube can contribute to the development of polite language in children if accompanied by active parental guidance and exposure to age-appropriate content that carries positive values. This study provides implications for parents, educators, and policymakers to manage digital media consumption as a part of early childhood character education